Pengaruh Media Sosial Facebook Terhadap Penjualan Umkm Di Kabupaten Pringsewu Provinsi Lampung - Aldiyana, Wayan; Fihartini, Yuniarti; Ramelan, Mudji Rachmat (Jurnal Mirai Management, 2024)
Introduction/Main Objectives: This research aims to determine the influence of Facebook social media on MSMEs sales in Pringsewu Regency, Lampung Province. The research method used is quantitative. The sample in this study was 160 MSMEs originating from Pringsewu and engaged in the culinary sector. Sampling used purposive sampling technique and hypothesis testing was carried out using SPSS 2.0 for Windows. The research results show that there is a significant influence of Facebook Social Media on Sales. This is because if the use of Social Media is done effectively and accurately then sales will also increase. Keywords: Facebook Social Media, Sales, MSMEs